Response of N cycling to nutrient inputs in forest soils across a 1000–3000 m elevation gradient in the Ecuadorian Andes. Issue 3 (1st March 2015) - Baldos, Angelica P.; Corre, Marife D.; Veldkamp, Edzo
Abstract : Large areas in the tropics receive elevated atmospheric nutrient inputs. Presently, little is known on how nitrogen (N) cycling in tropical montane forest soils will respond to such increased nutrient inputs. We assessed how gross rates of mineral N production (N mineralization and nitrification) and microbial N retention (NH4 + and NO3 − immobilization and dissimilatory NO3 − reduction to NH4 + [DNRA]) change with elevated N and phosphorus (P) inputs in montane forest soils at 1000‐, 2000‐, and 3000‐m elevations in south Ecuador. At each elevation, four replicate plots (20 × 20 m each) of control, N (added at 50 kg N·ha −1 ·yr −1 ), P (added at 10 kg P·ha −1 ·yr −1 ), and combined N + P additions have been established since 2008. We measured gross N cycling rates in 2010 and 2011, using 15 N pool dilution techniques with in situ incubation of intact soil cores taken from the top 5 cm of soil. In control plots, gross soil‐N cycling rates decreased with increase in elevation, and microbial N retention was tightly coupled with mineral N production. At 1000 m and 2000 m, four‐year N and combined N + P additions increased gross mineral N production but decreased NH4 + and NO3 − immobilization and DNRA compared to the control. At 3000 m, four‐year N and combined N + P additions increased gross N mineralization rates and decreased DNRA compared to the control; although NH4 + and NO3 − immobilization in the N and N + P plots were not different from the control, these were lower than their respective mineral N production. At all elevations, decreased microbial N retention was accompanied by decreased microbial biomass C and C:N ratio. P addition did not affect any of the soil‐N cycling processes. Our results signified that four years of N addition, at a rate expected to occur at these sites, uncoupled the soil‐N cycling processes, as indicated by decreased microbial N retention. This fast response of soil‐N cycling processes across elevations implies that greater attention should be paid to the biological implications on montane forests of such uncoupled soil‐N cycling.